Reverse Spin‐Crossover and High‐Pressure Kinetics of the Heme Iron Center Relevant for the Operation of Heme Proteins under Deep‐Sea Conditions1. (11th September 2014) - Troeppner, Oliver; Lippert, Rainer; Shubina, Tatyana E.; Zahl, Achim; Jux, Norbert; Ivanović‐Burmazović, Ivana
Abstract By design of a heme model complex with a binding pocket of appropriate size and flexibility, and by elucidating its kinetics and thermodynamics under elevated pressures, some of the pressure effects are demonstrated relevant for operation of heme‐proteins under deep‐sea conditions. Opposite from classical paradigms of the spin‐crossover and reaction kinetics, a pressure increase can cause deceleration of the small‐molecule binding to the vacant coordination site of the heme‐center in a confined space and stabilize a high‐spin state of its Fe center. This reverse high‐pressure behavior can be achieved only if the volume changes related to the conformational transformation of the cavity can offset the volume changes caused by the substrate binding. It is speculated that based on these criteria nature could make a selection of structures of heme pockets that assist in reducing metabolic activity and enzymatic side reactions under extreme pressure conditions.